Hybrid model of tourism recommendation software development (2022)
Technological progress implies a revolution for many economic sectors. Among them, the tourism industry is one of the activities that depend on the online interaction of users as a promotion and marketing strategy. Recommender systems have gained great importance as an engine to promote visits to tourist sites according to certain user preferences. This study proposes a hybrid development model that addresses software that provides information about tourist sites, cultural and historical interest of any city. The hybrid methodology is based on the classic waterfall model and the agile Scrum and Kanban methodologies, which allows incorporating the linear sequential scheme, but with the advantages of agile methodologies. The hybrid methodology was applied to the analysis and planning phase of the tourist recommendation software case study. Different functionalities were proposed aimed at providing information on the most important aspects for tourists. The proposed model maintains the cascading sequential structure, taking organizational and methodological aspects of the Scrum and Kanban proposal. Additionally, the software application proposal will allow the user to have an experience where they obtain multiple options, from budgeting trips to planning them, in the same application.